OTIMIZAÇÃO E APLICAÇÃO DE METODOLOGIA ANALÍTICA UTILIZANDO CLAE/FL PARA MONITORAMENTO DE FÁRMACOS ANTIBACTERIANOS FLUOROQUINOLÔNICOS EM ÁGUAS DO RIO ANIL LOCALIZADO NA CIDADE DE SÃO LUÍS MA - Araujo, Karla Caroline Muniz de (2013)
Fluoroquinolone antibacterial agents are widely used for treatment of infectious diseases. These compounds and their metabolites are excreted through the urinary tract, reaching the environment and cause many health hazards, human and animal, besides providing bacterial resistance. Given this, it was carried out an optimization of a chromatographic method for determination of three fluoroquinolone antibiotics (CIPRO, LEVO and NORF) by HPLC/FL in waters of Anil River at São Luís City-MA. For this, the chromatographic parameters were optimized and the linear range was obtained by constructing analytical curves and subsequently calibration curves for each analyte. The most satisfactory chromatographic conditions for analysis were: Luna column (250 x 4.6 mm, 5 mm), mobile phase consisting of a mixture of Methanol/Buffer (0,04 M NaHPO4.H₂O adjusted to pH 3 with H3PO4 85%) in proportion 30/70 (v/v), isocratic mode, flow 1 mL.minˉ¹, monitored at wavelengths of 278 nm and emission 450 nm excitation. The LD of the method for compounds CIPRO, LEVO and NORF were 1,8199, 4,0967 and 0,7567 μg.Lˉ¹ respectively and LQ of the method was 5 μg.Lˉ¹ for all three analytes. The studies of recovery by SPE showed levels from 77,95 to 100,28% for all three analytes. Subsequently the methodology was applied in water samples from the Anil River, being detected none of the analytes under study. Were performed acute toxicity tests with the test organism C. silvestrii, with EC(I)50,48h average of 0,4656 mg.Lˉ¹ for CIPRO and 0,6788 mg.Lˉ¹ for LEVO.